La géographie des élections en Algérie, de 2007 à 2017 - Gilles Van Hamme (L’Année du Maghreb)
Electoral analysis tends to ignore the interest of electoral studies in authoritarian regimes or in systems with limited pluralism. However, it remains interesting to analyse the electoral behavior of elections whose stake is not access to power, since we can observe a variety of forms of opposition to power or, conversely, better understand the networks on which power can rely. It is precisely the aim of this article to characterize the socio-territorial configuration of the hegemonic forces in power as well as the opposition parties in Algeria between 2007 and 2017. The analysis is based on a systematic collection of data at the level of wilayas and municipalities, their mapping and their correlation with the social and economic characteristics of the different territories. This analysis leads to some interesting results. First, non-participation and spoiled or blank ballots show a fairly stable geography, more urban than rural. Secondly, the parties of the ruling bloc (FLN and RND) and those of the opposition show a very variable geography, making it impossible to identify electoral bastions, with the notable exception of support for some opposition parties in Kabylie. Finally, the power bloc was able to maintain itself in 2017 in 80% of the municipalities where it was in power, indicating its ability to maintain its influence from the local to the national level.In urban areas, support for power appears to be very limited, and opposition is characterised by very low voter turnout and the importance of spoiled or blank ballots. This spatial configuration is not specific to Algeria but is found in many closed political and electoral systems. It reflects the lack of support for the regime from urban popular classes and/or intellectual middle classes concentrated in large cities. Conversely, electoral participation and support for the government – even if it remains a minority in proportion to the voting-age population – are higher in rural and peripheral areas, although with considerable regional and local differences as illustrated by the example of Kabylie, a true stronghold of opposition to the government. This undoubtedly illustrates a certain ability of the government to mobilize part of the electorate through its networks. However, from this perspective, the analysis points to a contradiction. On the one hand, the ruling bloc is able to rely on local networks across much of the country, allowing it to maintain its hegemony over a large part of the local and national assemblies. On the other hand, electoral analysis highlights the lack of stability in the socio-territorial base of the ruling bloc.